Free space microwave characterization of silicon wafers for microelectronic applications / Zaiki Awang, Deepak Kumar Ghodgaonkar and Noor Hasimah Baba - Awang, Zaiki; Ghodgaonkar, Deepak Kumar; Baba, Noor Hasimah (Institute of Research, Development and Commercialisation (IRDC), 2005)
A contactless and non-destructive microwave method has been developed to characterize silicon semiconductor wafers from reflection and transmission measurements made at normal incidence using MNDT. The measurement system consists of a pair of spot-focusing horn lens antenna, mode transitions, coaxial cables and a vector network analyzer (VNA). In this method, the free-space reflection and transmission coefficients, S11 and S21 are measured for silicon wafers sandwiched between two Teflon plates of 5mm thickness which act as a quarter-wave transformer at mid-band. The actual reflection and transmission coefficients, S11 and S21 of the silicon wafers are then calculated from the measured S11 and S21 using ABCD matrix transformation in which the complex permittivity and thickness of the Teflon plates are known. From the complex permittivity, the resistivity and conductivity can be obtained. Results for ptype and n-type doped silicon wafers are reported in the frequency range of 11 – 12.5 GHz. The dielectric constant of silicon wafer obtained by this method agrees well with that measured in the same frequency range by other conventional methods.